Strong Interactions of Hadrons at High Energies Gribov Lectures on Theoretical Physics - Gribov, Vladimir (Cambridge University Press, 2009)
Vladimir Gribov was one of the founding fathers of high-energy elementary particle physics. This volume derives from a graduate lecture course he delivered in the 1970s. It provides graduate students and researchers with the opportunity to learn from the teaching of one of the twentieth century's greatest physicists. Its content is still deeply relevant to modern research, for example exploring properties of the relativistic theory of hadron interactions in a domain of peripheral collisions and large distances that quantum chromodynamics has barely approached. In guiding the reader step-by-step from the basics of quantum mechanics and relativistic kinematics to the most challenging problems of high-energy hadron interactions with simplifying models and physical analogies, it demonstrates general methods of addressing difficult problems in theoretical physics. Covering a combination of topics not treated elsewhere, this 2008 title has been reissued as an Open Access publication.